2013
DOI: 10.7824/rbh.v12i2.211
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica de herbicidas aplicados em pré-emergência sobre palha de cana-de-açúcar em diferentes regimes hídricos

Abstract: Resumo -A manutenção da cobertura morta sobre o solo pode reduzir o potencial de infestação de plantas daninhas, assim como pode afetar a transposição dos herbicidas, a dinâmica de molhamento e a lavagem da palha pela água das chuvas. O trabalho teve como objetivos avaliar a dinâmica dos herbicidas diuron, metribuzin e tebuthiuron em diferentes regimes hídricos com e sem palha, e apontar as principais relações entre a presença ou ausência de palha na remoção dos herbicidas pela água da chuva e influência na ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
(10 reference statements)
1
9
0
2
Order By: Relevance
“…The best results in I. triloba and E. heterophylla regarding the number of plants (Tables 3 and 4) are those in which the (Prado et al, 2010;Rossi et al, 2013).…”
Section: Indaziflammentioning
confidence: 99%
See 1 more Smart Citation
“…The best results in I. triloba and E. heterophylla regarding the number of plants (Tables 3 and 4) are those in which the (Prado et al, 2010;Rossi et al, 2013).…”
Section: Indaziflammentioning
confidence: 99%
“…When there is no rainfall after herbicide application, this species control is impaired. Studies by Prado et al (2010) have shown that a 20 mm rainfall simulation after application of herbicides diuron, tebuthiuron and metribuzin is sufficient to percolate these herbicides of a straw layer of 10 t per hectare and provide a satisfactory control of I. triloba.…”
Section: Aminocyclopyrachlormentioning
confidence: 99%
“…However, straw becomes a problem, due to the barrier that hinders the contact of the product with the target-plant, leaving it vulnerable to volatilization and/or photolysis, until it leaches to the soil (Locke and Bryson, 1997). Rain is the main responsible for the transport of herbicide from the straw surface to soil; the first 20 mm are the ones representing the maximum transportation capacity of the herbicide (Toledo et al, 2009;Rossi et al, 2013;Prado et al, 2013). The transport of herbicide from the straw to the soil depends on the straw ability to cover soil and retain the herbicide, on the physicalchemical characteristics of the herbicide, on environmental conditions and on the period during which the area remains with no rain after the application (Silva and Monquero, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Entre as frações da MO do solo, as substâncias húmicas são os principais sorventes dos herbicidas (OLIVEIRA, 2011). Quanto maior o valor Kow do herbicida, maior seu potencial de retenção em superfícies hidrofóbicas, como a MO do solo (maior grau de humificação) (OLIVEIRA, 2011;PRADO et al, 2013). Na literatura científica há relatos Assim como o oxyfluorfen, a degradação do linuron é influênciada pela atividade microbiológica do solo (GRENNI et al, 2009;CYCOŃ et al, 2010).…”
Section: Linuronunclassified